The value of H.S. Skovoroda’s philosophical fables in the practice of fairy tale therapy - Kazachiner, O.; Boychuk, Yu.; Halii, A. (New Collegium, 2022)
The article clarifies that H. Skovoroda’s fables are broad on the issue, they raise the following issues: the boundaries of white and black, light and dark, good and evil, “related” work as a basic principle of work ethic, religiosity, the choice between good and evil, life and death, and so on. According to H. Skovoroda, the fable should help in the search for and discovery of eternal truth, his fables were aimed at exposing social ills, raised the spirit of civic dignity, the cult of reason, punished the world of abuse, deception, careerism, noble arbitrariness, veneration, profit, boasting, stupidity. H. Skovoroda’s fables are philosophical miniatures, reflections on related work, happiness and gratitude, which should fill every moment of a wise person’s life. But above all, these are good and funny stories about animals who are cunning, lazy, afraid and tear their noses like real people. The heroes of fairy tales show how important it is to see not only the external but also the internal essence of things, to take up the cause to which you have the ability, not to deceive others and value time and so on. As H. Skovoroda’s philosophical fables raise many life issues and problems that occur in the life of an adult, they are useful interesting and useful material in the practice of fairy tale therapy for adults.On the example of some fables “The Bee and the Hornet”, “The Dog and the Wolf” from the series “Fables of Kharkov” it is proved that it is appropriate to use such forms, methods and technologies of working with H. Skovoroda’s fables: discussion and analysis of fables, its leading ideas, retelling the work on behalf of its various characters, watching videos, drawing illustrations, as well as creating your own fables with a similar plot.